Humpuukia ja hulluutta Uuden taiteen vastaanotto 1910-luvun Suomessa - Siukonen, Jyrki (Tietolipas, 2023)
If the artworld is a battlefield of meanings, the fortunes of discourse did not favour avant-garde art in Finland in the 1910s. The latest trends, introduced by German and Russian artists in three pioneering exhibitions in Helsinki in 1914 and 1916, were dismissed by the Finnish press as foolish and unworthy. This book researches the contemporary reactions and contents of these exhibitions. The works shown in Helsinki included masterpieces from artists such as Chagall, Jawlensky, Kandinsky, Marc, Münter and Rozanova. Today these works can be found in the collections of leading museums in Europe, Russia and the USA. From the Finnish perspective, the turndown in the 1910s proved effective and irreversible. Never again have the local collections had similar opportunities to make a purchase. The rejection of radical international developments and emphasis on narrow nationalistic views left Finnish art lagging behind. This trend was already apparent in 1917 in St. Petersburg, where the Finnish artists were celebrated but their paintings deemed sombre and superannuated.